Singhealth and SMU partner to train undergraduates in health economics and management - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
SingHealth and the Singapore Management University (SMU) are embarking on a partnership to train the university’s undergraduates in the new Health Economics and Management (HEM) second major. Dr Amy Khor, Senior Minister of State for Health witnessed the inking of the Memorandum of Understanding (MOU) between the partners today at the opening ceremony of the Singapore Healthcare Management Congress.